Investigation of palpable udder defects in non-dairy ewes : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science, Massey University, Palmerston North, New Zealand - Zeleke, Mandefrot Meaza (Massey University, 2023)
Udder defects have been associated with low survival rates and reduced live weight gains in pre-weaned lambs and increased pre-mature culling of ewes. However, there are gaps in our understanding of the pathology of udder defects and changes that may occur over time. To address these issues three studies were undertaken. Chapter 4 describes the effect of palpable udder defects (hard or lump) on milk production and composition, while Chapter 5 assesses changes in udder half defects over time. In chapter 6, aerobic bacterial species were identified, and in Chapter 7 the gross and histological lesions associated with palpable udder defects were described. Milk yield was reduced by more than 50% in defective udder halves; however, the whole udder milk yield depended on the persistence and type of the defect and contralateral udder half compensatory increase. Udder half defects changed over time in lactation and during the non-lactating period. Udder halves categorised as hard or lump at pre-mating were more likely (Relative risk ratio (RRR= 6.8-1440) to be defective at some time in the future, within the same year or in the following season, compared to the udder halves categorised as normal. Mannheimia haemolytica and Streptococcus uberis were identified as dominant bacteria from defective udder halves while S. aureus was isolated from both defective and normal udder halves in similar proportions. Among several bacterial species identified during lactation, Mannheimia haemolytica, Staphylococcus xylosus, and Streptococcus pluranimalium were more stable over time. Udder halves categorised as hard was described as moderately enlarged and contained a single large abscess on dissection while typical histology showed the presence of pyogranuloma with extensive chronic inflammation and granulation tissue. The pathological changes in udder halves categorised as lump varied from normal appearance to severe chronic inflammation with a purulent exudate. In conclusion, due to an increased risk of future recurrence and long-term damage to the mammary tissue associated with udder halves categorised as hard, ewes with such defects should be culled. In contrast, udder halves categorised as lump showed marked pathological variation; therefore, additional studies are needed to determine more accurately, by sub-categorising and/or use of methods other than udder palpation (e.g., ultrasonography). Keywords: Bacteria, Change Over Time, Gross pathology and Histology, Milk Composition, Milk Yield, Palpable Udder Defect, Somatic Cell Counts.
Figure 2.4 is re-used under a Creative Commons CC-BY-NC-ND license.
Keywords: Ewes; Udders; Diseases; New Zealand; bacteria; change over time; gross pathology and histology; milk composition; milk yield; palpable udder defect; somatic cell counts; 300904 Veterinary diagnosis and diagnostics